Artificial Intelligence and HR: Challenges and Best Practices - Rashmi Singh, Neha Sharma, Ajay Jain (Journal of Informatics Education and Research, 2024)
Artificial intelligence (AI) in the workplace has a lot of prospects thanks to the marriage of robotics innovation, which includes AI and the Internet of Things (IoT). Precision, output, and adaptability are predicted to increase with Industry 5.0. The Human Resource (HR) function is one of the key areas where Industry 5.0 implementation calls for adjustments. Sector 5.0 gives companies a competitive edge by emphasizing HR. To address new challenges and expectations, HR needs to become more perceptive and flexible. We look into how AI may improve and digitize human resources in Industry 5.0. 271 HR experts from the administrative, industrial, and information technology (IT) sectors participated in our study, which examined five AI applications and HR readiness. Utilizing the Analysis of Moment Structures (AMOS) and the Statistical Package for Social Sciences (SPSS), our results highlight how crucial it is to look at hierarchical organizations in order to attain sustainable growth. The five AI applications for HR emphasized the flexibility and potential of people resources while highlighting the significance of safety and wellbeing in AI applications for HR.